ADAPTING TEXT TYPES AND REGISTERS - Mamatisakova Maftunakhan; Akhmedov Azimjon (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation. This article provides a comprehensive examination of the intricate process involved in adapting text types and registers to suit diverse communication contexts. It delves into the theoretical underpinnings, methodological approaches, and real-world implications of this practice. Through a thorough review of existing literature and the proposal of methodological frameworks, this article advances our understanding of how language adaptation influences the effectiveness of communication.